2020
DOI: 10.1111/1471-0528.16215
|View full text |Cite
|
Sign up to set email alerts
|

Increasing obstetric intervention for fetal growth restriction is shifting birthweight centiles: a retrospective cohort study

Abstract: Objective To assess the impact of increasing obstetric intervention on birthweight centiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Recalculating the birthweight centiles each decade to account for changes in population characteristics ensures that the charts remain an accurate descriptive representation of the population. However, it was recently reported that the effect of increasing intervention preferentially removing smaller babies from later gestations is likely to be the primary driver for shifting birthweight centiles [3]. Our observations in this study confirm this, illustrating that the proportion of births <3 rd and <10 th centile have decreased over time in each birthweight chart.…”
Section: Plos Onesupporting
confidence: 85%
See 4 more Smart Citations
“…Recalculating the birthweight centiles each decade to account for changes in population characteristics ensures that the charts remain an accurate descriptive representation of the population. However, it was recently reported that the effect of increasing intervention preferentially removing smaller babies from later gestations is likely to be the primary driver for shifting birthweight centiles [3]. Our observations in this study confirm this, illustrating that the proportion of births <3 rd and <10 th centile have decreased over time in each birthweight chart.…”
Section: Plos Onesupporting
confidence: 85%
“…Our observations in this study confirm this, illustrating that the proportion of births <3 rd and <10 th centile have decreased over time in each birthweight chart. That the effect was primarily at term gestations and not preterm gestations suggests that the shifting of centiles is an artefactual effect of increasing intervention, as previously suggested [3], rather than true biological increases in fetal size as a result of changing maternal characteristics.…”
Section: Plos Onementioning
confidence: 67%
See 3 more Smart Citations